2013
DOI: 10.3846/16111699.2012.732107
|View full text |Cite|
|
Sign up to set email alerts
|

Does a Connection Exist Among National Culture, Alliance Strategy, and Leading Ict Firms’ Performance?

Abstract: Abstract. In this paper we explore links among firms' performance, firms' alliance strategies, and national culture in the context of the global information and communication technologies (ICT) industry. Currently, partnering is the one of the most effective ways to access a broad set of resources. In the ICT industry, we can observe a significant number of alliances, networks, and mergers and acquisitions. The contribution of this paper is to investigate how a contextual factor -namely, national culture -infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…First, firms' performance prompts them to choose different cooperation strategies (Lant et al, 1992;Nohria and Gulati, 1996;Audia et al, 2000;Mezias et al, 2002;Fleming and Bromiley, 2003;Baum et al, 2005), such as a firm's propensity to engage in partnerships (Baum et al, 2005) and partner-selection strategies. Second, numerous characteristics of the context have been shown to play a role in shaping a firm's cooperation strategy; these characteristics include experienced uncertainty (Xie et al, 2012), national culture (Hofstede, 1984;Peng, 2005;Griffith et al, 2006;Siakas et al, 2010;Furres et al, 2012;Golonka and Rzadca, 2013) and generalized trust (Hofstede, 1984;Doney et al, 1998;Monczka et al, 1998;Young-Ybarra and Wiersema, 1999;Ibrahim and Ribbers, 2009).…”
Section: Formation Of Alliance Portfoliomentioning
confidence: 99%
See 3 more Smart Citations
“…First, firms' performance prompts them to choose different cooperation strategies (Lant et al, 1992;Nohria and Gulati, 1996;Audia et al, 2000;Mezias et al, 2002;Fleming and Bromiley, 2003;Baum et al, 2005), such as a firm's propensity to engage in partnerships (Baum et al, 2005) and partner-selection strategies. Second, numerous characteristics of the context have been shown to play a role in shaping a firm's cooperation strategy; these characteristics include experienced uncertainty (Xie et al, 2012), national culture (Hofstede, 1984;Peng, 2005;Griffith et al, 2006;Siakas et al, 2010;Furres et al, 2012;Golonka and Rzadca, 2013) and generalized trust (Hofstede, 1984;Doney et al, 1998;Monczka et al, 1998;Young-Ybarra and Wiersema, 1999;Ibrahim and Ribbers, 2009).…”
Section: Formation Of Alliance Portfoliomentioning
confidence: 99%
“…Studies have indicated that an extended, differentiated, complex, beneficial portfolio consisting of different alliances with various partners is a useful resource for carrying out a firm's strategy (Stuart, 2000;Lavie, 2007). A well-configured alliance portfolio has a positive impact on a firm's performance and innovativeness (Rothaermel, 2001;Rothaermel and Deeds, 2006;Shipilov, 2006;Lavie, 2007;Gulati, 2007;Duysters and Lokshin, 2011;Golonka, 2013;Golonka and Rzadca, 2013).…”
Section: Configuration Of Alliance Portfoliomentioning
confidence: 99%
See 2 more Smart Citations
“…Large evidence exists on the influence of national culture on people's value and perceptions, decision-making, strategy formulation, and inter-firm cooperation (Child and Faulkner, 1998). Consistently with previous research, we controlled for the two most significant dimensions of national culture as developed by Hofstede (1991) in predicting firm behavior and organization, that is, uncertainty avoidance and power distance (Golonka and Rzadca, 2013). To account for context-related factors potentially affecting alliance propensity and perceived performance (Rowley et al, 2000), we controlled for regulatory quality and rule of law countryindexes (Kaufmann et al, 2011).…”
Section: Controlsmentioning
confidence: 96%